Numerical investigations on vortex-ring collisions with heated sphere - Hoong, Jun Fong (Nanyang Technological University, 2023)
In this project, the flow field effects associated with the single vortex ring, colliding with a sphere of constant temperature, was studied numerically with ANSYS Fluent based on Large Eddy Simulations. A vortex ring of Reynold number 2000 and sphere-to-ring diameter ratios of 1 were used respectively. The heated sphere was set to a constant temperature of 363K to allow for heat transfer interactions with the vortex flow field. Formation of secondary and tertiary rings were observed. Both secondary and tertiary rings expand radially and leapfrogs the primary vortex ring. Due to the opposite vorticity between secondary/tertiary ring with primary vortex ring, the secondary/tertiary hairpin vortices wrap around the primary vortex ring, initiating azimuthal stability and leads to the breakdown to turbulence. Numerical study was also investigated for normal collision of vortex ring upon heated sphere with sphere-to-ring diameter ratios of 0.5. For this case, the tertiary vortex ring formed eventually break apart and did not wrap themselves around the primary vortex ring. This resulted in a relatively stable primary vortex ring as lesser instabilities effect were introduced due to absence of inviscid interaction between primary and tertiary vortex ring. Finally, the last simulation was done for collision of a vortex ring that was offset laterally upon heated sphere with sphere-to-ring diameter ratios of 1. For this case, the primary vortex ring merges with the boundary layer. The inviscid interaction between primary and secondary vortex ring is in a form of compression where the secondary ring compresses the primary ring causing it to breakdown into turbulence. This entire study will provide insight on how the heated spherical objects affect the flow field, possibly allowing existing designs and features to be improved on